2022
DOI: 10.5194/acp-22-14783-2022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of isoprene nitrate chemistry in detailed chemical mechanisms

Abstract: Abstract. Isoprene nitrates are important chemical species in the atmosphere which contribute to the chemical cycles that form ozone and secondary organic aerosol (SOA) with implications for climate and air quality. Accurate chemical mechanisms are important for the prediction of the atmospheric chemistry of species such as isoprene nitrates in chemical models. In recent years, studies into the chemistry of isoprene nitrates have resulted in the development of a range of mechanisms available for use in the sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 62 publications
5
15
0
Order By: Relevance
“…This requirement for very high O3 and low NOx means that we should expect very low concentrations of daytime INHE and INPE under typical urban conditions. This is consistent with modelling of Beijing which showed that while INHE may comprise a large fraction of night-time C5H9NO5 compounds, the daytime contribution is very small (Mayhew et al, 2022).…”
supporting
confidence: 91%
See 3 more Smart Citations
“…This requirement for very high O3 and low NOx means that we should expect very low concentrations of daytime INHE and INPE under typical urban conditions. This is consistent with modelling of Beijing which showed that while INHE may comprise a large fraction of night-time C5H9NO5 compounds, the daytime contribution is very small (Mayhew et al, 2022).…”
supporting
confidence: 91%
“…Model Validation As a test of the ability of the steady-state models to represent conditions present under ambient scenarios, the model results were compared to measurements collected in the summer of 2017 in Beijing. (Shi et al, 2019;Hamilton et al, 2021;Whalley et al, 2021;Reeves et al, 2021;Newland et al, 2021;Mayhew et al, 2022) The NOx mixing ratios measured in the afternoon periods in Beijing ranged between 5 ppb and 20 ppb, and O3 mixing ratios ranged from around 60 ppb to 140 ppb.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…The fraction of C4-5N group in gOON enhances slightly during daytime (Fig. S8e), which might be due to strong photochemical formation of isoprene-nitrates (Fisher et al, 2016;Reeves et al, 2020;Mayhew et al, 2022;Hamilton et al, 2021). The C8-10N fraction in total pOON slightly enhances during nighttime (Fig.…”
mentioning
confidence: 87%